Ruptured Median Raphe Cyst Mimicking a Vascular Penile Mass on Ultrasound - Amir Pakray; Andrew Surro; Donald Gibson; Ahmad Tahawi (Case Reports in Radiology)
Median raphe cysts are uncommon benign cysts thought to occur due to improper fusion of the genital tubercle and can occur anywhere along the median raphe, from the glans to the anus, most commonly occurring along the ventral penile shaft. Limited information is available in the literature about the common imaging features of median raphe cysts with available reports highlighting an avascular cystic lesion. Our case demonstrates a 10-year-old male patient presenting with a ventral penile mass that demonstrated interval growth in the absence of trauma without overlying skin changes. Doppler ultrasound examination demonstrated a solid vascular mass measuring up to 1.6 cm at the ventral aspect of the penis with arterial and venous waveforms. The patient underwent elective resection of the mass which revealed a 2.0 cm inflamed glandular subtype median raphe cyst. This report demonstrates an atypical imaging presentation of an inflamed median raphe cyst, particularly that of a heterogeneous solid mass with arterial and venous blood flow on ultrasound.